Integration of oral health into primary health care system: views of primary health care workers in Lagos State, Nigeria - Matilda Braimoh; Eyitope Ogunbodede; Abiola Adeniyi (AOSIS, 2014)
The limited access to oral health care in developing countries can be greatly improved by integrating oral health into the Primary Health Care (PHC) system. This study was designed to assess the views of PHC workers on integrating oral health care into the PHC system. A self-administered questionnaire survey was conducted in two selected local government areas of Lagos State. The instrument contained three sections assessing sociodemographic features, knowledge of common oral diseases and views on integration of oral health into PHC respectively. The mean knowledge score was 7.75 (SD=±1.81), while 60.4% of the respondents had average knowledge scores. Educational status (P=0.018) and designation (P=0.033) were significantly related to the mean knowledge scores. There was no significant difference in the oral health knowledge of the various cadres (P=0.393). Majority (85.4%) of the respondents were willing to include oral health education in their job schedule and 82% believed they needed more training on oral health. The knowledge of the respondents on the causes of the common oral diseases was deficient. Oral health education should be included in the future curriculum of these personnel.